Is China a Deviant Case? A Societal-Level Test of the Modernization Theory. - Zhou, Yingnan Joseph (Political Studies, 2021)
Some view China as a deviant case to the modernization theory. This view is based on two observations. First, the Chinese middle class shows no distinct democratic orientations. Second, one's trust in the Chinese Communist Party regime rises as he or she gets financially better off. However, the modernization theory by its nature is a societal-level theory, and it has not yet been tested at the societal level in China. This study undertakes this task by examining the relationship between a province's economic development and its political trust in the central government and its tolerance of public criticism of the government. The two provincial-level variables are estimated by Multilevel Regression and Poststratification using data from China Survey 2008, CGSS 2010, 2012, 2013, and the 2010 National Census. The results, which are corroborated by county-level Multilevel Regression and Poststratification, strongly support the modernization theory.